2023
DOI: 10.2459/jcm.0000000000001569
|View full text |Cite
|
Sign up to set email alerts
|

Modern tools in congenital heart disease imaging and procedure planning: a European survey

Marvin Iannotta,
Fabio Angelo d’Aiello,
Alexander Van De Bruaene
et al.

Abstract: Aims Congenital heart diseases (CHDs) often show a complex 3D anatomy that must be well understood to assess the pathophysiological consequences and to guide therapy. Three-dimensional imaging technologies have the potential to enhance the physician's comprehension of such spatially complex anatomies. Unfortunately, due to the new introduction in clinical practice, there is no evidence on the current applications. We conducted a survey to examine how 3D technologies are currently used among CHD Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…All these types of XR-based technologies can be very helpful in the field of cardiology [34][35][36] (also see Table 1). Marvin et al [37] have shown that this approach is quite popular in European cardiology, although it has not led to routine practice. For example, VMersive (VR-Learning, Poland) is an automated tool dedicated to the reconstruction of CT and MRI image scenes.…”
Section: Extended Reality In Cardiologymentioning
confidence: 99%
See 1 more Smart Citation
“…All these types of XR-based technologies can be very helpful in the field of cardiology [34][35][36] (also see Table 1). Marvin et al [37] have shown that this approach is quite popular in European cardiology, although it has not led to routine practice. For example, VMersive (VR-Learning, Poland) is an automated tool dedicated to the reconstruction of CT and MRI image scenes.…”
Section: Extended Reality In Cardiologymentioning
confidence: 99%
“…A further important area of XR-based technology consists of the education (broadly understood) of both future medical staff and patients [69][70][71], as in the case of teaching heart anatomy [37]. For example, VR-based simulators provide an effective tool for determining the heart's mechanical and electrical activities [72].…”
Section: Extended Reality In Cardiologymentioning
confidence: 99%